Legal protection of Jathilan Lancur Art as a form of traditional cultural expression - Syahrin, Savira Alfi; Novanto, Richardus (Privietlab, 2025)
This research examines the urgency of the legal protection of Jathilan Lancur art as a form of traditional cultural expression that is vital to the lives of the people of Yogyakarta. Jathilan Lancur not only functions as a means of traditional ceremonies such as merti desa and clean villages that foster mutual cooperation, but also reflects fundamental values in the form of prayer, gratitude, and enthusiasm for life. The legal protection of this art is crucial, based on Law No. 28/2014 on Copyright and Law No. 5/2017 on the Promotion of Culture. These two regulations confirm Jathilan Lancur’s status as a traditional cultural expression (EBT) that must be inventoried and preserved by the state. The research method applied in this study is juridical-sociological, which examines this protection concretely realized through various initiatives and roles of the Head of the Yogyakarta Special Region Culture Office, including inventory, coaching, organizing festivals, strengthening communities, utilizing technology, and developing regional regulations with the active involvement of the community in three kapanewon in Sleman Regency-Cangkringan (through Kridha Turangga Jati Jiwosari), Kalasan (Turangga Agung & Sekar Mudha Turangga). Sekar Mudha Turangga), and Minggir (Turangga Lancur Jati)-led by maestros, are strong evidence of collaboration in maintaining and inheriting Jathilan Lancur. Thus, legal protection is not just a formality but a guarantee of the sustainability of Jathilan Lancur as an invaluable cultural identity.